From Faith to Strength: How Parental Religiosity Enhances the Character Strength of Adolescents with Down Syndrome through Strength-Based Parenting - Sumiati, Neneng Tati; Idriyani, Natris; Ein, Indy Hurun; Syukrilla, Wara Alfa (JURNAL PSIKOLOGI, 2024)
Understanding character strengths in adolescents with Down Syndrome (DS) can help identify positive aspects and develop intervention programs so that they have a better quality of life. This study aims to examine the influence of parental religiosity on the character strength of adolescents with DS which is mediated by strength-based parenting (SBP). The participants in this research consisted of 70 parents of teenagers with Down syndrome in Jakarta and the surrounding area, who were obtained through purposive sampling. Research variables were measured by adapting and modifying the Values in Action Inventory of Strength (VIA-IS), Brief Multidimensional Measurement of Religiousness/Spirituality (BMMR/S), and Strength-based Parenting (SBP) scale. Data analysis was carried out using regression-based mediation analysis via the PROCESS syntax in IBM SPSS. The results showed that SBP could significantly mediate the influence of parental religiosity on the character strength of adolescents with DS (indirect effect =.4916; 95% CI=(.265; .8042)). The implication of this research is that parents of adolescents with DS are advised to increase their religiosity and use SBP so that the character strengths of adolescents with DS develop optimally.